An Uncommon Instance of Squamous Cell Carcinoma of the Buccal Mucosa in a Kidney Transplant Recipient - Hardik Sharma; Vandana Thakur; Anupam Thakur (Indian Journal of Transplantation, 2025)
Patients undergoing solid organ transplants are more at risk than the entire population for developing a broad spectrum of neoplasia due to their ongoing immunosuppressive conditions. This article details a 44-year-old man’s case of squamous cell carcinoma (SCC) in his tongue following a kidney transplant from a live donor. During the posttransplant phase, he showed many comorbidities while taking multiple medicines. One of these, hypertension, is quite common in organ-transplanted individuals. In this specific case, the oral cavity is the primary site of neoplasia. We describe one such instance in which the patient experienced a functional kidney transplant for 12 years, but then developed SCC of the buccal mucosa.